The Role of Fetal Kidney Length and Fetal Transverse Diameter of Heart in Prediction of Gestational Age - Subrat, Panda; Sankar, Rudrapal Gouri; Ananya, Das; Surajit, Ray Baruah; Nalini, Sharma (International Journal of Innovative Research in Medical Science, 2020)
Objective: Currently there is no single ultrasonological parameter for accurate estimation of gestational age in third trimester. The present study is undertaken to validate the fetal kidney length and fetal transverse diameter of heart measurement as a measurement of fetal growth with less variability. Materials & Methods: It is a cohort study conducted in Department of Obstetrics and Gynaecology, NEIGRIHMS from 2015 to 2016. 224 women with singleton pregnancies and sure of LMP were enrolled. Each woman underwent minimum three ultrasonographic measurements- at first trimester for gestational age by CRL, at second trimester with fetal conventional biometry, at third trimester with Fetal kidney length, transverse diameter of heart and fetal conventional biometric parameters and analysed with SPSS Version22. Results: The gestational age with CRL was within three days of the menstrual age. In second trimester, conventional parameter (BPD,HC,AC,FL) were better parameters. Conventional parameter did not correspond to gestational age calculated from LMP. (BPD, R2= 0.4819, HC R2- 0.507, AC R2- 0.5175, FL R2-0.5243, Combined Conventional parameter R2- 0.5888). Fetal kidney length (R2-0.8356) and transverse diameter of heart (R2-0.8795) better correlated with gestational age. Conclusion: Kidney length and transverse diameter of heart are better predictors of gestational age in third trimester.